Relationship between occupation and education with the choice of IUD contraception in Pauh District, Padang City, West Sumatra. - Fitri Khoiriyah; Ariadi; Yusrawati; Laila Rahmi (Institute of Computer Science (IOCS), 2022)
High population growth is a significant problem faced by the Indonesian people in the field of population. Efforts to create quality families are primarily targeted at controlled population growth and increasing the quality of small families, as indicated by the increased use of rational, effective, and efficient contraceptive methods, namely the use of Long-Term Contraceptive Methods (MKJP). Referring to the 2020-2024 BKKBN Strategic Plan, the BKKBN vision has been set: